Comparison Between NSAID and Intra-articular Corticosteroid Injection in Frozen Shoulder of Diabetic Patients; a Randomized Clinical Trial - Dehghan, A.; Pishgooei, N.; Salami, M.-A.; zarch, S.M. M.; Nafisi-moghadam, R.; Rahimpour, S.; Soleimani, H.; Owlia, M. B. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Frozen shoulder or adhesive capsulitis is a relatively common encountered musculo-skeletal disease in which arouses following soft tissue involvement of glenohumeral joint and presents with pain and limitation of shoulder’ active and passive motions.The incidence of frozen shoulder among diabetic patients is about 10–20%, stiffness in such patients is more severe and should be managed actively.Local Glucocorticoid injection, NSAIDs and physiotherapy each can relief the symptoms. The aim of this study was to compare the efficacy of glenohumeral injection of Glucocorticoid with NSAIDs in frozen shoulder of diabetic patients.The randomized clinical trial study conducted during Feb 2009-Aug 2010 on diabetic patients with frozen shoulder that were referred to rheumatology and endocrinology clinics, Yazd, Iran. Diagnostic criteria of capsulitis were pain of shoulder and range of motion limitation in all directions. The patients were divided into 2 groups, patients of first group received NSAID while the latter group were undergone intra-articular corticosteroid injection. After 1 week, home exercise was done for both group and evaluation of the patients after first visit was done likewise 2nd, 6th, 12th and 24th weeks. All registered data were transformed into SPSS-15 software and analyzed.Totally 57 patients (19 males (33.3%) and 38 females (66.7%) were included in the analysis. There was no significant difference between sex (P=0.4) and age (P=0.19) of patients.No significant relation was detected between 2 groups after 24 weeks according to range of motion in flexion (P=0.51), abduction (P=0.76), external rotation (0.12) and internal rotation (P=0.91). Also any significant difference in pain score was not detected (P=0.91).Based on our study, both intra-articular corticosteroid and NSAID are effective in treatment of adhesive capsulitis and there is no significant difference between efficacies of these 2 treatment modalities in diabetic patients.
Keywords: frozen shoulder; intra-articular injection; NSAID